Polarity Effect on the Electronic Structure of Molybdenum Dichalcogenides MoXY (X, Y = S, Se): A Computational Study Based on Density-Functional Theory - Salsabila Amanda Putri; Edi Suharyadi; Moh. Adhib Ulil Absor (Universitas Gadjah Mada, 2021)
Computational research based on the Density Functional Theory (DFT) has been performed to explore the electronic structure of monolayer material Transition Metal Dichalcogenides (TMDCs) Molybdenum Dichalcogenides MoXY (X; Y = S; Se) in the first Brillouin zone by breaking its mirror symmetry due to the polarity effect. Our study discovered that Rashba spin-splitting could be identified around the Γ point by proposing the polarity effect on the system. Moreover, the anisotropic characteristic of Rashba spin-splitting in this system can be explicitly analyzed by using perturbation theory and the third-order symmetry group analysis. By performing the spin textures analysis, this research also recognizes the in-plane direction of spin textures. The tunable characteristic of the Rashba parameter of this monolayer polar MoSSe system under the strain effects control exhibits its potential to be the candidate of semiconductor material for the Spin Field Effect Transistor (SFET) device.